Supply Chain Management (SCM) Perspectives, Practices, and Strategies: A Private and Public Sector Comparative Study - Hafiza Al Haya Sarfaraz; Dr. Noman Ahsan; Muhammad Ajmal; Erum Mateen (Indus Journal of Social Sciences, 2025)
This examination explores the variations in perceptions of supply chain management (SCM) techniques, topics, tools, and strategies among procurement professionals in public and private sector businesses. To achieve this, a survey was performed among procurement experts from a Fortune 100 company and a municipal employer in Pakistan. The accrued statistics were analyzed to evaluate differences in SCM perceptions in the sample and whether these variations correlated with formal schooling stages. Key findings screen that public sector procurement specialists generally tend to understand SCM as a constrained characteristic centered on shopping, while their sector opposite numbers view it as a strategic manner requiring move-purposeful coordination. Public sector respondents suggested lower stages of formal education compared to those inside the private sector. The study additionally found that SCM-associated subjects, equipment, and strategies maintain greater importance for private-sector experts than for the ones inside the public sector. However, respondents from both sectors acknowledged the important role of ethics and moral behaviour in powerful SCM practices.